Medical Treatment of Cushing's Disease: An Overview of the Current and Recent Clinical Trials - Pivonello, Rosario; Ferrigno, Rosario; De Martino, Maria Cristina; Simeoli, Chiara; Di Paola, Nicola; Pivonello, Claudia; Barba, Livia; Negri, Mariarosaria; De Angelis, Cristina; Colao, Annamaria (Frontiers in Endocrinology, 2020)
Cushing's disease (CD) is a serious endocrine disorder characterized by chronic hypercortisolism, or Cushing's syndrome (CS), caused by a corticotroph pituitary tumor, which induces an excessive adrenocorticotropic hormone (ACTH) and consequently cortisol secretion. CD presents a severe clinical burden, with impairment of the quality of life and increase in mortality. Pituitary surgery represents the first-line therapy, but it is non-curative in one third of patients, requiring additional treatments. Among second-line treatments, medical therapy is gradually gaining importance, although the current medical treatments are unable to reach optimal efficacy and safety profile. Therefore, new drugs and new formulations of presently available drugs are currently under clinical investigation in international clinical trials, in order to assess their efficacy and safety in CD, or in the general population of CS. Among pituitary-directed agents, pasireotide, in the twice-daily subcutaneous formulation, has been demonstrated to be an effective treatment both in clinical trials and in real-world studies, and extension studies of the phase II and III clinical trials reported evidence of long-term efficacy with general good safety profile, although associated with frequent hyperglycemia, which requires monitoring of glucose metabolism. Moreover, the most recent once-monthly intramuscular formulation, pasireotide long-acting release (LAR), showed similar efficacy and safety, but associated with potential better compliance profile in CD. Roscovitine is an experimental drug currently under investigation. Among adrenal-directed agents, metyrapone is the only historical agent currently under investigation in a prospective, multicenter, international clinical trial, that would likely clarify its efficacy and safety in a large population of patients with CS. Osilodrostat, a novel agent with a mechanism of action similar to metyrapone, seems to offer a rapid, sustained, and effective disease control of CD, according to recently completed clinical trials, whereas levoketoconazole, a different chemical formulation of the historical agent ketoconazole, is still under investigation in clinical trials, with preliminary evidences showing an effective and safe control of CS. ATR-101 is an experimental drug currently under investigation. Among glucocorticoid receptor-directed drugs, mifepristone has been demonstrated to improve clinical syndrome and comorbidities, especially hypertension and impairment of glucose metabolism, but the occurrence of hypokalemia and in women uterine disorders, due to the concomitant action on progestin receptor, requires caution, whereas the preliminary evidence on relacorilant, characterized by high selectivity for glucocorticoid receptor, suggested good efficacy in the control of hypertension and impairment of glucose metabolism, as well as a good safety profile, in CS. Finally, a limited experience has demonstrated that combination therapy might be an interesting approach in the management of CD. The current review provides a summary of the available evidences from current and recent clinical trials on CD, with a specific focus on preliminary data.